Does Diffusion Tensor Tractography of the Corticospinal Tract Correctly Reflect Motor Function? - Min, Zhi-gang (Med Princ Pract, 2014)
OBJECTIVE: To investigate the consistency of diffusion tensor tractography of the corticospinal tract on motor function. CLINICAL PRESENTATIONS AND INTERVENTION: Three patients with brain tumor were admitted to our hospital with impaired motor function. Diffusion tensor imaging (DTI) and tractography were performed in these patients to assess their affected corticospinal tract. The corticospinal tract showed interruption with moderately impaired motor function in 2 patients. The third case had significantly weakened muscle strength on the left upper limb but an intact right corticospinal tract. CONCLUSION: These cases showed that the corticospinal tracts obtained by DTI with tractography were inconsistent with motor function. Hence, DTI should be interpreted with caution.